Salinomycin decreases doxorubicin resistance in hepatocellular carcinoma cells by inhibiting the β-catenin/TCF complex association via FOXO3a activation - Zhou, Yue (Oncotarget, 2015)
Doxorubicin is a conventional and effective chemotherapy drug against hepatocellular carcinoma (HCC). However, during long-term doxorubicin monotherapy, HCC cells may eventually develop acquired-resistance to doxorubicin which results in recurrence and a poor prognosis. Salinomycin, an ionophore antibiotic, was recently reported to selectively kill human cancer stem cells (CSCs) which were response for chemoresistance. In this study, salinomycin was found to exert synergistic cytotoxicity with doxorubicin in HCC cells and be capable of inhibiting doxorubicin-induced epithelial-mesenchymal transition (EMT), an important cellular process involved in the acquired chemoresistance of tumors. Further experiments revealed that FOXO3a, a multifunctional transcription factor that can be activated by salinomycin, was vital in mediating doxorubicin-induced EMT. In addition, activated FOXO3a disturbed the interaction between β-catenin and TCF and inhibited the expression of β-catenin/TCF target genes (ZEB1, c-Myc and CyclinD1), which played important roles in doxorubicin-induced EMT in HCC cells. Finally, the enhanced curative efficacy of combination treatment of doxorubicin and salinomycin for HCC was confirmed in established xenograft models. In summary, the present study identifies a new doxorubicin-based chemotherapy for advanced HCC and provides a potential anti-cancer strategy targeting FOXO3a and related cell pathway molecules.